Penerapan Analisis SWOT dalam Evaluasi Mutu Lembaga Bimbingan Belajar: Studi Kasus Di Bimbel Aletheia di Poris, Tangerang - Shyta Patrilia Chandra; Hotmaulina Sihotang (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the application of SWOT analysis in quality evaluation and to formulate quality improvement strategies at the Aletheia tutoring institution in Poris, Tangerang. The research method used was a descriptive qualitative approach with a literature study design. Data sources included relevant literature and internal secondary data from the institution. These data were analyzed through the stages of identifying internal factors (strengths and weaknesses), external factors (opportunities and threats), developing a SWOT matrix, and formulating strategies. The results indicate that the institution's main strengths lie in strong teamwork, stakeholder communication, and organic promotion. While weaknesses include suboptimal digital promotion, limited infrastructure, and teacher resources, opportunities stem from a conducive environment, increasing student numbers, and interest in Mandarin programs. Threats include competition from other tutoring institutions and resistance from the surrounding community. The study concludes that SWOT analysis is an effective quality evaluation tool for formulating targeted improvement strategies, including strengthening governance, enhancing human resource quality, developing digital promotion, and managing community relations to maintain the institution's sustainability and competitiveness.   Keywords: Quality, Tutoring, Educational Strategy, Institutional Management